Efficient Validation and Source Aloofness in Wireless Sensor Networks (International Journal of Engineering and Computer Science, 2015)
Message authentication is one of the most effective ways to thwart unauthorized and corrupted messages from being forwarded inwireless sensor networks (WSNs). For this reason, many key management techniques have been developed for message authentication, basedon either symmetric-key cryptosystems or public-key cryptosystems. Most of the authentication schemes have the limitations of security, inaddition to lack of scalability and resilience to node compromise attacks. To address these issues, a polynomial-based scheme was recentlyintroduced. The polynomial schemes have the weekness to build in threshold value determined by the degree of the polynomial. In theproposed system, a scalable authentication scheme is SAMA based Modified Elgamal Signature (MES). It enabling intermediate nodesauthentication and allows any node to transmit an unlimited number of messages without suffering the threshold problem. In addition thisscheme can also provide message source privacy